The measurement of proprioceptive accuracy: A systematic literature review - Horváth, Á.; Ferentzi, E.; Schwartz, K.; Jacobs, N.; Meyns, P.; Köteles, F. (Journal of Sport and Health Science, 2023)
Background Proprioceptive accuracy refers to the individual's ability to perceive proprioceptive information, that is, the information referring to the actual state of the locomotor system, which originates from mechanoreceptors located in various parts of the locomotor system and from tactile receptors located in the skin. Proprioceptive accuracy appears to be an important aspect in the evaluation of sensorimotor functioning; however, no widely accepted standard assessment exists. In this systematic review, our goal was to identify and categorize different methods that are used to assess different aspects of proprioceptive accuracy.